Potential effect of FLASH radiotherapy on testicular damage: a review of current evidence - Zhi, Xiaoyu; Du, Lehui; Han, YaNan; Li, Weiwei; Zhang, Pei; Guo, Xingdong; Wang, Yuan; Ma, Na; Lei, Xiao; Qu, Baolin (Frontiers in Oncology, 2025)
Radiotherapy is a major source of ionizing radiation that adversely affects the male reproductive system. FLASH radiotherapy (FLASH-RT), a novel technique delivering ultra-high dose rate (UHDR) radiation, has shown promise in reducing normal tissue damage while maintaining antitumor efficacy—a phenomenon known as the “FLASH effect”. Male fertility depends on the coordinated function of spermatogenic, Sertoli, and Leydig cells in the testes, which display differential sensitivity to radiation exposure. Due to ethical limitations in human studies, rodent models are indispensable for exploring radiation-induced testicular injury. This review summarizes current evidence of the FLASH effect across rodent organs and the impact of ionizing radiation at different dose rates on testicular cells. Given the current lack of direct evidence for the FLASH effect in testicular tissue, it also reviews mechanisms observed in other organs that may contribute to its potential protective role in the testes. A deeper understanding of these mechanisms could inform fertility-preserving strategies in male cancer patients receiving radiotherapy.